Postoperative Pain Is Associated With Psychological and Physical Readiness to Return to Sports One-Year After Anterior Cruciate Ligament Reconstruction - Marcel Betsch, M.D., M.H.B.A; Graeme Hoit, M.D; Tim Dwyer, M.B.B.S., Ph.D; Daniel Whelan, M.D., M.Sc; John Theodoropoulos, M.D., M.Sc; Darrell Ogilvie-Harris, M.D; Jaskarndip Chahal, M.D., M.Sc., M.B.A (Elsevier, 2021)
Purpose: To identify whether any patient factors, injury factors, or symptom severity scores are associated with either psychological or physical readiness to return to sport after anterior cruciate ligament reconstruction (ACLR). Methods: Consecutive patients with an ACL injury that required surgical treatment were included in this study. All patients completed the single-legged hop testing and the Anterior Cruciate Ligament Return to Sport Index (ACL-RSI) at 1 year postoperatively. Multivariable regression analysis models were used to determine whether an independent relationship existed between baseline patient factors (age, sex, BMI, preinjury Marx Activity Score), injury factors (meniscal tear and chondral injury), physical symptoms (Knee Injury and Osteoarthritis Outcome Score [KOOS] for pain and symptoms), and the dependent variables of physical and psychological readiness to return to sport (single-legged hop and ACL-RSI). Results: Of the 113 patients who were included, 37% were female, and the mean age of our population was 28.2 years (SD = 8.1). Multivariable regression models demonstrated that patient-reported pain symptoms at 1 year postoperatively, as measured by the KOOS pain subscale, was significantly associated with both ACL-RSI score (Beta estimate: 1.11 [95% CI: .62-1.60] P < .001) and the ability to pass the single-legged hop test (OR: 1.07 [95% CI: 1.004-1.142] P = .037). Conclusions: Patients with higher reported pain levels at 1 year following ACLR have lower psychological and physical readiness to return to sport. Level of Evidence: Level 3, retrospective cohort study.